Ida M. Tarbell : the woman who challenged big business-- and won! - McCully, Emily Arnold (Clarion Books/Houghton Mifflin Harcourt, 2014)
Tarbell was the catalyst for exposing the truth behind corruption and unfair business practices. She investigated and published works about the Standard Oil Trust for McClure's Magazine that informed the world of shady business dealings and skyrocketed her into the public eye. She wrote inspiring and engaging biographies on public figures, her most notable on Abraham Lincoln. Although largely forgotten as the country forged into the 20th century, her writing of the truth lives on.